Does Familial Aggregation of Chronic Low Back Pain Affect Recovery?: A Population-Based Twin Study. Issue 17 (1st September 2017) - Zadro, Joshua R.; Shirley, Debra; Sánchez-Romera, Juan F.; Ordoñana, Juan R.; Ferreira, Paulo H.
Abstract : Study Design: Longitudinal twin-cohort study. Objective: To investigate the effect familial aggregation of chronic low back pain (LBP) has on the recovery from chronic LBP. Summary of Background Data: LBP is a worldwide problem, with pain and disability often becoming chronic. Genetics and familial behaviors could significantly affect the recovery from chronic LBP but have not been extensively investigated. Methods: A total of 624 Spanish twins from the Murcia Twin Registry reported experiencing chronic LBP within the past 2 years during the 2009/11 data collection wave and were followed up in 2013. Familial aggregation of chronic LBP was determined by the co-twin experiencing chronic LBP within the past 2 years at baseline. Twins reporting LBP "within the past 4 weeks" at follow-up were considered to have not recovered. Results: There were 455 twins with available data on LBP at follow-up and available data on LBP from their co-twin at baseline. Twins with an affected co-twin at baseline were significantly more likely to have not recovered from chronic LBP at follow-up (odds ratio [OR] = 1.6, 95% confidence interval [CI]: 1.0–2.4, P  = 0.046). This relationship was stronger for monozygotic twins (OR = 2.5, 95% CI: 1.3–4.8, P  = 0.006) (n = 172) but disappeared when considering only dizygotic twins (OR = 1.1, 95% CI: 0.6–2.0, P  = 0.668) (n = 283). Sibling-relative recurrence risk ( λ s ) was 1.2 for the total sample, 1.5 for monozygotic twins, and 1.1 for dizygotic twins. Conclusion: Having a sibling with chronic LBP at baseline increased the likelihood of LBP at follow-up by 20%, with this likelihood increasing to 50% if the sibling was an identical twin. These results are novel and highlight the important influence genetics have on people's recovery from chronic LBP. Information regarding the presence of chronic LBP within a family is easy to obtain and has the potential to inform clinicians on which patients are less likely to recover when treatment implementation is not considered. Level of Evidence: 3